2014
DOI: 10.1167/14.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Spatial biases in viewing behavior

Abstract: Viewing behavior exhibits temporal and spatial structure that is independent of stimulus content and task goals. One example of such structure is horizontal biases, which are likely rooted in left-right asymmetries of the visual and attentional systems. Here, we studied the existence, extent, and mechanisms of this bias. Left- and right-handed subjects explored scenes from different image categories, presented in original and mirrored versions. We also varied the spatial spectral content of the images and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 147 publications
(175 reference statements)
19
107
0
Order By: Relevance
“…However, a recent attentional model introduced by Takio, Koivisto, and Hämäläinen (2014) suggests that a right visual field advantage occurs in both linguistic and nonlinguistic spatial attention tasks due to lateralized processing of linguistic stimuli, as well as asymmetries in attentional, bottom-up neural processes (see also Robertson, 2004). This account can be further distinguished from other higher level, cultural accounts, which suggest a left-to-right attentional bias in a variety of different paradigms, though the interpretations of this bias have been somewhat mixed (see Ossandon, Onat, & Konig, 2014, for a review). One interpretation suggests that visuospatial asymmetries along the horizontal axis are critically modulated by directional oculomotor routines associated with reading and writing.…”
Section: Resultsmentioning
confidence: 92%
“…However, a recent attentional model introduced by Takio, Koivisto, and Hämäläinen (2014) suggests that a right visual field advantage occurs in both linguistic and nonlinguistic spatial attention tasks due to lateralized processing of linguistic stimuli, as well as asymmetries in attentional, bottom-up neural processes (see also Robertson, 2004). This account can be further distinguished from other higher level, cultural accounts, which suggest a left-to-right attentional bias in a variety of different paradigms, though the interpretations of this bias have been somewhat mixed (see Ossandon, Onat, & Konig, 2014, for a review). One interpretation suggests that visuospatial asymmetries along the horizontal axis are critically modulated by directional oculomotor routines associated with reading and writing.…”
Section: Resultsmentioning
confidence: 92%
“…It has indeed been shown that viewers have a leftward bias in starting scene inspection (Dickinson & Intraub, 2009;Foulsham & Kingstone, 2010;Nuthmann & Matthias, 2014;Ossandón, Onat & König, 2014). In the "original" (evaluated) orientation, two scenes had both objects in the left half, two had both objects in the right half, while the remaining had one object in each side.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with other studies documenting asymmetries in left-right fixation distribution (Nuthmann & Matthias, 2014;Ossandón et al, 2014), we used a dynamic task in which the repeated presentation was concealed. Therefore, participants had to sustain their attention and adjust their eye movements accordingly over the course of the trial, and they had smaller freedom to look at the remaining parts of the display, which were not relevant for the task.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MOT, if people track a group of targets as a single object (Yantis, 1992), we should expect no left-right difference, since the optimal viewing position is found at the center of the perceived object, with no lateral bias (Foulsham & Kingstone, 2010). Conversely, others have reported a preference for early fixations to the left part of the scene (Dickinson & Intraub, 2009;Foulsham, Gray, Nasiopoulos, & Kingstone;2013;Nuthmann & Matthias, 2014;Ossandón, Onat, & König, 2014). This bias is often discussed with respect to Bpseudoneglect^: a leftward bias in the line-bisection task in healthy humans (Bowers & Heilman, 1980;Jewell & McCourt;2000).…”
mentioning
confidence: 98%
See 1 more Smart Citation